Sirt3 Ameliorates Oxidative Stress and Mitochondrial Dysfunction After Intracerebral Hemorrhage in Diabetic Rats - Zheng, Jingwei; Shi, Ligen; Liang, Feng; Xu, Weilin; Li, Tao; Gao, Liansheng; Sun, Zeyu; Yu, Jun; Zhang, Jianmin (Frontiers in Neuroscience, 2018)
Aims: Sirtuin3 (sirt3) plays a pivotal role in improving oxidative stress and mitochondrial dysfunction which directly induced neuronal apoptosis after intracerebral hemorrhage (ICH). Reactive oxygen species (ROS) is also a critical activator in triggering NACHT, LRR and PYD domains-containing protein 3 (NLRP3) inflammasomes activation which can regulate inflammatory responses in brain. Moreover, Hyperglycemia can aggravate the ICH-induced damage. Hence, this study was designed to investigate the mechanisms of neuroprotection of sirt3 in hyperglycemic ICH. Methods: ICH model was established by autologous blood injection. Hyperglycemia was induced by intraperitoneal injection with streptozotocin. Honokiol (HKL, a pharmacological agonist of sirt3) was injected intraperitoneally at doses of 2.5, 5, or 10 mg/kg. Sirt3 small interfering RNA transfection was implemented through intracerebroventricular injection. The expression of sirt3 and its downstream signaling molecules were detected using Western blotting or Immunofluorescence staining. Morphological changes of mitochondria were detected by electron microscopy. SH-SY5Y cells were incubated with 10μM oxyhemoglobin for 48 hours to establish an in vitro ICH model, and then JC-1 staining was used to determine mitochondrial membrane potential (Δψm). Results: Hyperglycemia could suppress sirt3 expression after ICH when compared with non-diabetic rats. Sirt3 protein expression was decreased to the minimum at 24h in perihematoma tissues. Electron microscope analysis indicated that hyperglycemic ICH induced extensive mitochondrial vacuolization. HKL attenuated ROS accumulation, adenosine triphosphate (ATP) reduction and Δψm through Sirt3-SOD2 and Sirt3-NRF1-TFAM pathway. Sirt3 knockdown could exacerbate the neuronal apoptosis and reverse the positive effects of HKL. Sirt3 activation could decrease NLRP3 and IL-1β levels through deacetylating SOD2 and scavenging ROS. Conclusion: HKL protects against hyperglycemic ICH-induced neuronal injury via a sirt3 dependent manner. Key words: ICH hyperglycemia sirt3 mitochondrial dysfunction oxidative stress